Perkembangan Kelembagaan Dari Negeri Dan Marga Menjadi Desa Di Kecamatan Tungkal Ulu Kabupaten Tanjab Barat Provinsi Jambi - Erdianto ' (Fakultas Hukum Universitas Riau, 2011)
Reveals the historical development of the village or clan named country means also discuss the history of the law on setting up an autonomous region in the smallest administrative structure Indonesia. This paper concluded a few things about the growth and development of villages in the District of West Tanjab Tungkal Ulu Jambi Province. Adjustment system according to the form of the village who live in actual Java stunt capability for autonomous villages.